REDISTRIBUTION, INEQUALITY AND POLITICAL CONFLICT - Patricia Justino
This paper analyses the relationship between redistributive policies and civil unrest. This relationship is modelled in a discrete two-period recursive model. Key theoretical assumptions and outcomes are tested empirically using data for a panel of 14 major Indian states between 1973 and 2000. The analysis shows that, in the medium-term, redistributive policies have been significantly more effective in reducing civil unrest in India than more direct solutions, such as the use of police and military forces, and have resulted in important positive externalities on economic growth. This represents an important lesson for countries where social cohesion tends to break frequently but large-scale wars may be avoidable